2011
DOI: 10.1007/s10750-011-0897-8
|View full text |Cite
|
Sign up to set email alerts
|

The introduced bivalve Limnoperna fortunei boosts Microcystis growth in Salto Grande reservoir (Argentina): evidence from mesocosm experiments

Abstract: In order to assess the effects of the introduced bivalve Limnoperna fortunei on watercolumn properties of Salto Grande reservoir, experiments were conducted using six 400 L mesocosms: 2 with 100 mussels, 2 with 300 mussels, and 2 controls (without mussels). At 0, 1, 2, 3, 7, 14, 21, 28, and 35 days we measured nutrient and chlorophyll a concentrations, counted and identified the phytoplankton, and estimated the density, size, and number of cells of the colonies of Microcystis spp. Cumulative periphyton growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 58 publications
4
48
1
3
Order By: Relevance
“…Differences between this and our study may be explained by differences in the mesocosm dimensions, in the characteristics of the water and the type of formulation applied. Cataldo et al (2012b) reported enhanced growth of periphyton in mesocosm experiments with L. fortunei, which is consistent with our results. Moreover, Pizarro et al (2015a) observed that the active ingredient and L. fortunei acted synergistically on an already established periphytic community (mussels alone and technical-grade glyphosate alone induced a significant increase in periphytic chlorophyll a).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Differences between this and our study may be explained by differences in the mesocosm dimensions, in the characteristics of the water and the type of formulation applied. Cataldo et al (2012b) reported enhanced growth of periphyton in mesocosm experiments with L. fortunei, which is consistent with our results. Moreover, Pizarro et al (2015a) observed that the active ingredient and L. fortunei acted synergistically on an already established periphytic community (mussels alone and technical-grade glyphosate alone induced a significant increase in periphytic chlorophyll a).…”
Section: Discussionsupporting
confidence: 93%
“…Three mesocosms had two cages of plastic mesh with 5-mm pore size containing 100 mussels, which were suspended below the water surface (treatment M). Thus, mussel density lies within the range recorded for natural water-bodies (Boltovskoy et al 2009) and is high enough to observe the effect of mussels, as previously assessed in experimental studies with mesocosms (Cataldo et al 2012b;Pizarro et al 2015b). Three mesocosms were treated with technical-grade glyphosate acid (gly) at 6 mg L −1 (≥95 % purity; CAS: 1071-83-6) (treatment G).…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results indicate that this mussel primarily fed on particles between 500 and 40 9 10 3 lm 3 , which is consistent with the observation made by Rojas Molina et al (2010). In view of the importance of high biovolume algae as a food item, we expect that the feeding activity of the mussel in its natural environment will lead to an over-dominance of small biovolume algae or even encourage the development of algae that aggregate in mucilaginous colonies as a strategy to avoid mussel predation (Cataldo et al 2012).…”
Section: Selectivity Multi-criteriamentioning
confidence: 99%
“…Em virtude da expansão do mexilhão dourado em rios da América do Sul, são reportados inúmeros prejuízos na esfera ambiental dos ecossistemas aquáticos colonizados, como indícios de alterações nas concentrações e proporções de nutrientes, mudanças na estrutura das comunidades fitoplanctônicas e favorecimento da manutenção de florações de cianobactérias (CATALDO et al, 2012). Alguns autores também relatam que a presença de L. fortunei nos ambientes colonizados já o torna parte da dieta alimentar de algumas espécies de peixes do rio Paraná e do Rio da Prata (CANTANHÊDE et al, 2008;VERMULM JUNIOR & GIAMAS, 2008;PAO-LUCCI et al, 2010).…”
Section: Mexilhão Douradounclassified